2020
DOI: 10.1111/conl.12752
|View full text |Cite
|
Sign up to set email alerts
|

Field sizes and the future of farmland biodiversity in European landscapes

Abstract: Lower diversity of plant and animal farmland species are usually reported where cropland has been aggregated into larger fields, which raises prospects of curbing declines in European farmland biodiversity and associated ecosystem services by halting trends to field size increases associated to agricultural intensification, without having to set aside arable land for conservation. Here, we consider the factors underlying trade-offs between farmer income and biodiversity as mediated by field size at local and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 90 publications
2
56
0
1
Order By: Relevance
“…We described agricultural intensification (hereafter AI) using the following variables: cover of small woody features, open, and woodland RH and mean field size. These were previously shown to be important for farmland birds (Clough et al., 2020; Fahrig et al., 2015; Šálek et al., 2018).…”
Section: Methodsmentioning
confidence: 88%
“…We described agricultural intensification (hereafter AI) using the following variables: cover of small woody features, open, and woodland RH and mean field size. These were previously shown to be important for farmland birds (Clough et al., 2020; Fahrig et al., 2015; Šálek et al., 2018).…”
Section: Methodsmentioning
confidence: 88%
“…These five indicators cover important processes of farm size growth and specialization, which are two key drivers of agricultural intensification (van Vliet et al 2015). At the landscape level, we chose to quantify agricultural field size, since this is an indicator of land management intensity with implications for biodiversity (Geiger et al 2010;Clough et al 2020), as well as total agricultural area and proportion of intensively used agricultural land (Billeter et al 2008).…”
Section: Indicators To Characterize Agricultural Developmentmentioning
confidence: 99%
“…A number of studies have shown that small crop fields benefit biodiversity (e.g., [8,11,12,40,41]). Fahrig et al [11] investigated the abundance and biodiversity of birds, plants, butterflies, syrphids, bees, carabids, and spiders in different agricultural landscapes, and found that field size had a strong effect on biodiversity.…”
Section: Revenues For Promoting Ecosystem Services 271 Biodiversity I...mentioning
confidence: 99%
“…Questions to be answered concern support amount per linear metre, maximum amount per hectare, the legal definition of 'perimeter', differentiations between crops and regions, etc. As pointed out by Clough et al [8], there is a large potential for reducing the economic-biodiversity trade-off associated with small fields by using new technologies such as small fossil-free autonomous vehicles.…”
Section: Impact Of Payments For Environmental Benefits On Profitabilitymentioning
confidence: 99%
See 1 more Smart Citation